2014
DOI: 10.1111/jog.12363
|View full text |Cite
|
Sign up to set email alerts
|

Additional surgical risk factors and patient characteristics for mesh erosion after abdominal sacrocolpopexy

Abstract: In abdominal sacrocolpopexy operations in which polypropylene meshes are used, stage 3 or 4 prolapse, concomitant hysterectomy and three or more additional procedures increase the risk of mesh exposure development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…patients related to SUI only; and the remaining 2 533 patients in 11 studies [13,14,18,21,24,[31][32][33]36,37,41] had POP/SUI, with 1 105 of them receiving both POP and SUI procedures concomitantly. Of all eligible studies, two were randomised controlled trials (RCTs) [16,39], four were prospective cohort studies [23,32,34,35], one study consisted of a RCT and a prospective cohort study [17], three were retrospective casecontrol studies [18,21,42], and 15 were retrospective cohort studies [13][14][15]19,20,22,24,30,31,33,[36][37][38]40,41]. Of the 25 studies, nine were conducted in the USA; three in France; three in China; two each in the UK, Australia, and Turkey; one each in Chinese Taipei, Sweden, Switzerland, and the Netherlands.…”
Section: Statistics Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…patients related to SUI only; and the remaining 2 533 patients in 11 studies [13,14,18,21,24,[31][32][33]36,37,41] had POP/SUI, with 1 105 of them receiving both POP and SUI procedures concomitantly. Of all eligible studies, two were randomised controlled trials (RCTs) [16,39], four were prospective cohort studies [23,32,34,35], one study consisted of a RCT and a prospective cohort study [17], three were retrospective casecontrol studies [18,21,42], and 15 were retrospective cohort studies [13][14][15]19,20,22,24,30,31,33,[36][37][38]40,41]. Of the 25 studies, nine were conducted in the USA; three in France; three in China; two each in the UK, Australia, and Turkey; one each in Chinese Taipei, Sweden, Switzerland, and the Netherlands.…”
Section: Statistics Analysismentioning
confidence: 99%
“…age, parity, and menopausal status), mesh materials, surgical procedures, operation histories and concomitant diseases (e.g. diabetes mellitus and hypertension) [13][14][15][16][17][18][19][20][21][22][23][24]. However, most risk factors remain controversial owing to the relative few patients in each study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported that smoking, concomitant hysterectomy, estrogen replacement therapy (ERT), and an advanced stage of POP might increase the risk of vaginal mesh erosion after SCP [10][11][12][13][14][15]. However, these studies had some methodologic limitations (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, until now, a better alternative has not been available. [3][4][5][6][7] The effectiveness of a biologic patch has been the subject of much debate. 8 The current author has data collected from June 2012 to December 2017 on patients, each of whom underwent laparoscopic sacrocolpopopexy with a biologic patch consisting of a non-crosslinked ADM (Life Cell now under the ownership of Allergan).…”
Section: Introductionmentioning
confidence: 99%